2y+(y-3)=18-2(y+3)

Simple and best practice solution for 2y+(y-3)=18-2(y+3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2y+(y-3)=18-2(y+3) equation:


Simplifying
2y + (y + -3) = 18 + -2(y + 3)

Reorder the terms:
2y + (-3 + y) = 18 + -2(y + 3)

Remove parenthesis around (-3 + y)
2y + -3 + y = 18 + -2(y + 3)

Reorder the terms:
-3 + 2y + y = 18 + -2(y + 3)

Combine like terms: 2y + y = 3y
-3 + 3y = 18 + -2(y + 3)

Reorder the terms:
-3 + 3y = 18 + -2(3 + y)
-3 + 3y = 18 + (3 * -2 + y * -2)
-3 + 3y = 18 + (-6 + -2y)

Combine like terms: 18 + -6 = 12
-3 + 3y = 12 + -2y

Solving
-3 + 3y = 12 + -2y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '2y' to each side of the equation.
-3 + 3y + 2y = 12 + -2y + 2y

Combine like terms: 3y + 2y = 5y
-3 + 5y = 12 + -2y + 2y

Combine like terms: -2y + 2y = 0
-3 + 5y = 12 + 0
-3 + 5y = 12

Add '3' to each side of the equation.
-3 + 3 + 5y = 12 + 3

Combine like terms: -3 + 3 = 0
0 + 5y = 12 + 3
5y = 12 + 3

Combine like terms: 12 + 3 = 15
5y = 15

Divide each side by '5'.
y = 3

Simplifying
y = 3

See similar equations:

| f-3,1,4f(2)=30 | | 40x=100+15x | | 4x+8=2x+34 | | 8x-2+9+7x=37 | | 4y+3(y-8)=7y-2(y-10) | | N+9=5*3 | | -2a-3+a+7= | | 6x+3-2x=9+6 | | 2n(4n+2)=8n | | -3x-12=-12 | | 8v+23=3(v+1) | | 2x(4n+2)=8n | | y+0.4=0.8(y-2) | | x^2+28+196=0 | | .25(n+9)+.10(n+9)+5+.05n=3.75 | | 9x-4=9(x+7) | | 11+2y=6(y+1)+y | | (4x^3)+(3x^2)+2=0 | | 3x-7x+7=x-6+13 | | 7+(9+k)=84 | | X^3-3x^2-24x+17=0 | | 3(x-2)+5x=6x-8 | | 6x+x=42 | | 4(N-10)=6n+2 | | 4(N-10)=6 | | 11a+9*22=294 | | 11a+9c=294 | | 4(3x+2)(2x-7)= | | -u^2+9u+26=0 | | 10x+3=3(3x+7) | | x+-22-10y=-5 | | 11a+9c=780 |

Equations solver categories